2017
DOI: 10.3390/rs9080768
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation for China’s Planned CO2-IPDA

Abstract: Active remote sensing of atmospheric XCO 2 has several advantages over existing passive remote sensors, including global coverage, a smaller footprint, improved penetration of aerosols, and night observation capabilities. China is planning to launch a multi-functional atmospheric observation satellite equipped with a CO 2 -IPDA (integrated path differential absorption Lidar) to measure columnar concentrations of atmospheric CO 2 globally. As space and power are limited on the satellite, compromises have been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…At the beginning, the requirement on the random error of monthly XCO 2 product acquired by the CO 2 -IPDA equipped on AEMS is below 0.3% with spatial resolutions of 50 km and 100 km over lands and oceans, respectively. Our previous study has already suggested that such a requirement can be fulfilled in most areas in China and its surroundings [33]. It is worth noting that the requirement on measurements of XCO 2 using remote sensing was defined as 2.5 ppm (~0.7%@360 ppm) on a 8 • × 10 • footprint in 2001 [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the beginning, the requirement on the random error of monthly XCO 2 product acquired by the CO 2 -IPDA equipped on AEMS is below 0.3% with spatial resolutions of 50 km and 100 km over lands and oceans, respectively. Our previous study has already suggested that such a requirement can be fulfilled in most areas in China and its surroundings [33]. It is worth noting that the requirement on measurements of XCO 2 using remote sensing was defined as 2.5 ppm (~0.7%@360 ppm) on a 8 • × 10 • footprint in 2001 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several performance modeling studies of a spaceborne greenhouse-gas-IPDA LIDAR system have been performed in the past decade [33,[39][40][41]. However, the cloud coverage issues have never been integrated into the performance models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, atmospheric CO 2 observation mainly relies on passive detection technology, especially passive satellite remote sensing technology. Representative systems include Japan's Greenhouse Gases Observing Satellite (GOSAT) [1], NASA's Orbiting Carbon Observatory-2 (OCO-2) [2,3], and China's carbon satellite [4,5], which all have wide detection ranges, large monitoring areas, and large sampling data. Since the successful launch of GOSAT in January 2009, several teams of scholars from more than 10 countries have been working on independent retrievals of XCO 2 and XCH 4 with errors of less than 2 ppm Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is appropriate now to assess the feasibility of global Lidar observations of point sources that could complement the current and future observation systems, and to discuss the implications for a novel space-borne IPDA Lidar which goes beyond the systems currently being designed and developed [19][20][21][22][23]. In this initial feasibility study we first introduce the IPDA method focusing on plume detection sensitivity in Section 2, and use a Lidar performance model to assess the required size of a satellite Lidar for plume detection in Section 3.…”
Section: Introductionmentioning
confidence: 99%